Distribution of Avifauna in Aketajawe Lolobata National Park Based on Zone and Land Cover Typology - Supratman , Supratman Tabba; Nurrani, Lis Nurrani (Jurnal Wasian, 2016)
Aketajawe Lolobata National Park (TNAL) is a protected area for paradise birds, parrots and others North Maluku endemic wildlife. As a former of commercial logging concessions, this areas have been damaged and loss of wildlife habitat. The purpose of this research was to determine bird species of TNAL area based on zone category, this research is important in order to validate data related to the birds species diversity. Data collection used the observation point system with purposive sampling by direct observation and audio. The number of observation points were six points in core zone, ten points in both of jungle and traditional zone, and six points in buffer zone. Research showed that there are 39 species found in the buffer zone, 45 species in jungle and traditional zone, and 19 species in core zone. Wallace’s standardwing (Semioptera wallacei) is one of the 15 endemic species of North Maluku was found along drummer rail (Habroptila wallacii) which is Halmahera’s endemic species. Distribution pattern of birds in TNAL is very varied. The jungle and traditional zone have the amount and the highest species diversity while the highest species variation was in the buffer zone. The natural habitat of bird in this area generally located in open area along former road skid as well as forest edge and only a few were found in primary forest of core zone.